2013
DOI: 10.1063/1.4825230
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of undoped ZnO thin film via plasma enhanced atomic layer deposition and its application for an inverted polymer solar cell

Abstract: We studied the tuning of structural and optical properties of ZnO thin film and its correlation to the efficiency of inverted solar cell using plasma-enhanced atomic layer deposition (PEALD). The sequential injection of DEZn and O2 plasma was employed for the plasma-enhanced atomic layer deposition of ZnO thin film. As the growth temperature of ZnO film was increased from 100 °C to 300 °C, the crystallinity of ZnO film was improved from amorphous to highly ordered (002) direction ploy-crystal due to self cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…The resulting GPC is $1.5 Å / cycle, which is comparable to reported values for the GPC of PE-ALD ZnO films using DEZ and O 2 -plasma at the lowest temperatures investigated [28][29][30][31][32] [($2.0 Å /cycle at 100 C, 28 $1.7 Å /cycle at 100 C, 29 $2.5 Å /cycle at 100 C, 30 $1.5 Å / cycle at 100 C, 31 and $1.9 Å /cycle at 75 C (Ref.…”
Section: A Determination Of Saturation Regimessupporting
confidence: 73%
See 3 more Smart Citations
“…The resulting GPC is $1.5 Å / cycle, which is comparable to reported values for the GPC of PE-ALD ZnO films using DEZ and O 2 -plasma at the lowest temperatures investigated [28][29][30][31][32] [($2.0 Å /cycle at 100 C, 28 $1.7 Å /cycle at 100 C, 29 $2.5 Å /cycle at 100 C, 30 $1.5 Å / cycle at 100 C, 31 and $1.9 Å /cycle at 75 C (Ref.…”
Section: A Determination Of Saturation Regimessupporting
confidence: 73%
“…Several groups have been investigating the material properties and growth behavior of ZnO films grown by PE-ALD adopting DEZ as the metal precursor, and oxygen or waterfed plasmas as oxidative coreactants. 1,[28][29][30][31][32][33] A wide range of GPC values has been obtained, spreading from 1.5 to 3 Å / cycle at substrate temperatures of 75-300 C. The GPC values are clues for different growth mechanisms which cannot be associated with pure ALD growth. It has been reported that the reason behind the variation of the ZnO growth characteristics could be attributed to precursor decomposition effects at substrate temperatures above 60 C, leading to nonself-limiting growth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter is in agreement with the trend observed in Figure 5f as the concentration of the hydrogen related O-H bonds decreases with the increasing plasma time. It is reported that both hydrogen and hydroxyl in ZnO behave as shallow donors and can lead to higher carrier concentration [22,23]. The reduction of the O-H bond concentration also leads to the decrease of the carrier concentrations presented in Figure 6.…”
Section: Zno Thin Filmsmentioning
confidence: 92%